2022
DOI: 10.1155/2022/7055045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laparoscopic Total Extraperitoneal Umbilical Hernia Repair on Incision Infection, Complication Rate, and Recurrence Rate in Patients with Umbilical Hernia

Abstract: The aim of this study is to clarify the influence of laparoscopic total extraperitoneal umbilical hernia repair on incision infection, complication rate, and recurrence rate in patients with an umbilical hernia (UH). Sixty-seven UH patients referred to our hospital from June 2017 to June 2019 were selected as the research participants. Thirty-six patients in the research group (RG) were treated with laparoscopic total extraperitoneal umbilical hernia repair, and the other 31 cases in the control group (CG) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this manner, a total of 43 studies were identified as potentially eligible, and a full analysis of their text was made. Thirty-five studies were excluded: one, because we could not have access to their full text in the absence of authors’ response to our contact [ 16 ], ten for having a non-randomized design [ 17 26 ], one for comparing the open and laparoscopic approach grouping multiple surgeries (ventral hernia repair, appendectomy, cholecystectomy, and bariatric surgery) [ 27 ], and twenty-three for including all kinds of ventral hernias: one Spigelian hernia [ 28 ] and twenty-two incisional hernias from which thirteen only included incisional hernias [ 29 – 41 ] and nine included incisional and primary ventral hernias combined in the analysis [ 42 50 ]. One study was included after the assessment of the references of included primary studies [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this manner, a total of 43 studies were identified as potentially eligible, and a full analysis of their text was made. Thirty-five studies were excluded: one, because we could not have access to their full text in the absence of authors’ response to our contact [ 16 ], ten for having a non-randomized design [ 17 26 ], one for comparing the open and laparoscopic approach grouping multiple surgeries (ventral hernia repair, appendectomy, cholecystectomy, and bariatric surgery) [ 27 ], and twenty-three for including all kinds of ventral hernias: one Spigelian hernia [ 28 ] and twenty-two incisional hernias from which thirteen only included incisional hernias [ 29 – 41 ] and nine included incisional and primary ventral hernias combined in the analysis [ 42 50 ]. One study was included after the assessment of the references of included primary studies [ 51 ].…”
Section: Resultsmentioning
confidence: 99%